Repetitive Facial Nerve Stimulation Using Occipitalis Muscle. Issue 4 (July 2017) - Adatepe, Turgut; Gündüz, Ayşegül; Yildirim, Ahmet; Uzun, Nurten
Abstract : Purpose: We aimed to evaluate the reliability and reproducibility of repetitive nerve stimulation recorded on occipitalis muscle by comparing recordings on nasalis muscle in healthy subjects. Methods: A total of 23 healthy subjects (mean age: 44.7 ± 13.8 years) underwent detailed neurological examination and repetitive nerve stimulation using nasalis and occipitalis muscles. Amplitude and area percentage changes of compound muscle action potentials (CMAPs) after repetitive nerve stimulation with different frequency were compared between right and left sides and between recordings on nasalis and occipitalis muscles. Results: Comparisons of percentage amplitude changes of nasalis and occipitalis CMAPs showed no differences (+0.1% ± 3.8% vs. +1.4% ± 3.9%, P = 0.129). Average area percentage change of nasalis CMAPs was 0.3% ± 19.0%, whereas the value of occipitalis CMAP was +2.8% ± 15.2% ( P = 0.851). Comparisons of nasalis and occipitalis CMAPs values showed no differences. Conclusions: The repetitive nerve stimulation recorded on occipitalis muscle is simple, easy to apply, noninvasive, consistent, and reproducible.